How visiting nurses detect symptoms of disease progression in patients with chronic heart failure - Chinatsu Taniguchi (International Journal of Qualitative Studies on Health & Well-Being, 2020)
Purpose: Chronic heart failure patients are often rehospitalized because they fail to seek appropriate, timely care. However, both patients and nurses experience difficulties in detecting signs of heart failure exacerbation. We aimed to qualitatively investigate how visiting nurses detect symptoms of disease progression in chronic heart failure patients in their homes. Methods: Participants were three experienced home-visit chronic heart failure nurses who completed one-to-one interviews. Data were analysed using the qualitative synthesis method (KJ method). Results: Six themes were identified that reflected detection of disease exacerbation and nursing support to prevent disease progression: difficulty of judging deterioration in patients with comorbidities; ascertaining conditions needing immediate intervention; detection of illness progression from changes in the patient’s appearance; inferring instability in physical condition from patients’ concerns and questions; arranging to ensure continued management of the patient post discharge; and instructing patients to ensure they never return to their old habits. Conclusions: The findings indicate that nurses experience challenges in detecting illness progression and judging when outpatient or hospital care is needed. However, nurses use a range of signs and symptoms to determine deterioration. Home-visit nurses thus play a crucial role in the post-hospital care of chronic heart failure patients.